Silica-associated systemic lupus erythematosus with lupus nephritis and lupus pneumonitis: A case report and a systematic review of the literature. Issue 7 (18th February 2022) - Fukushima, Kazuhiko; Uchida, Haruhito A.; Fuchimoto, Yasuko; Mifune, Tomoyo; Watanabe, Mayu; Tsuji, Kenji; Tanabe, Katsuyuki; Kinomura, Masaru; Kitamura, Shinji; Miyamoto, Yosuke; Wada, Sae; Koyanagi, Taisaku; et al.
Abstract: Introduction: Several epidemiological studies have shown that silica exposure triggers the onset of systemic lupus erythematosus (SLE); however, the clinical characteristics of silica-associated SLE have not been well studied. Patient concerns: A 67-year-old man with silicosis visited a primary hospital because of a fever and cough. His respiratory condition worsened, regardless of antibiotic medication, and he was referred to our hospital. Diagnosis: The patient showed leukopenia, lymphopenia, serum creatinine elevation with proteinuria and hematuria, decreased serum C3 level, and was positive for anti-double stranded DNA antibody, anti-nuclear antibody, and direct Coombs test. He was diagnosed with SLE. Renal biopsy was performed, and the patient was diagnosed with lupus nephritis (class IV-G(A/C) + V defined by the International Society of Nephrology/Renal Pathology Society classification). Computed tomography revealed acute interstitial pneumonitis, bronchoalveolar lavage fluid showed elevation of the lymphocyte fraction, and he was diagnosed with lupus pneumonitis. Interventions: Prednisolone (50 mg/day) with intravenous cyclophosphamide (500 mg/body) were initiated. Outcomes: The patient showed a favorable response to these therapies. He was discharged from our hospital and received outpatient care with prednisolone slowly tapered off. He had cytomegalovirus and herpes zoster virus infections during treatment, which healed with antiviral therapy. Review: We searched for the literature on sSLE, and selected 11 case reports and 2 population-based studies. The prevalence of SLE manifestations in sSLE patients were comparative to that of general SLE, particularly that of elderly-onset SLE. Our renal biopsy report and previous reports indicate that lupus nephritis of sSLE patients show as various histological patterns as those of general SLE patients. Among the twenty sSLE patients reported in the case articles, three patients developed lupus pneumonitis and two of them died of it. Moreover, two patients died of bacterial pneumonia, one developed aspergillus abscesses, one got pulmonary tuberculosis, and one developed lung cancer. Conclusion: Close attention is needed, particularly for respiratory system events and infectious diseases, when treating patients with silica-associated SLE using immunosuppressive therapies.